Reliability of a new time-motion analysis model based on technical-tactical interactions for wrestling competition - López-González, D. E.; Miarka, B. (International Journal of Wrestling Science, 2013)
The aim of the study was to determine the reliability of a new Time-Motion Analysis (TMA) model based on technical-tactical interactions in the three Olympic wrestling styles: freestyle (FS), female wrestling (FW) and Greco-Roman (GR). Two raters, one of them an expert researcher in performance analysis, and the other an active senior wrestler and national level referee, separately analyzed a sample composed of 2 video-recorded combats per style (N=6) downloaded from FILA´s World Senior Championships `11 WebTV site, using eleven categories as indicators for classification and to determine the duration of the wrestlers actions in both activity and rest time. Inter-rater reliability tests Cohen´s Kappa and Intra-class Correlation Coefficient (ICC) were used as Agreement Measures in order to assess the categorical and duration data. Resulting values were classified as "substantial" for categorical agreement per style and and "almost perfect" for agreement in duration and score-related actions. These results indicate that this new TMA model can be considered reliable when being used by different raters.